The Effect of Service Quality and E-Service Quality on Customer Satisfaction in Bukit Vista Hospitality Customers - I Putu Gede Dipta Pradnyana (Universitas Ciputra Surabaya, 2023)
In the current digital era, service quality has developed into e-service quality (E-SERVQUAL) which contributes passively and actively to services through electronic media to facilitate service delivery to consumers. Bukit Vista Hospitality is a hospitality villa management company that utilizes conventional and online services to support its services to consumers to be able to provide a competitive advantage in the market. The study used quantitative methods by collecting data for 208 respondents using purposive sampling technique which was analyzed using multiple linear regression analysis using IBM SPSS 22 software. The results showed that service quality and e-service quality had a positive and significant influence on customer satisfaction. Hypothesis testing states that service quality and e-service quality have a partial and simultaneous relationship to customer satisfaction. The results also show that service quality and e-service quality have an effect of 35.4% on customer satisfaction. It is recommended that Bukit Vista Hospitality improve its services because it is found that service quality and e-service quality have a positive influence on customer satisfaction so it is very relevant to improve services in this aspect in order to create much better customer satisfaction.